4 - Hegemony and Spatial Politics: The Press and the Struggle for Lagos in Colonial Nigeria: DOI: 10.4314/ad.v29i4.22207 - Adebanwi, Wale (Africa Development, 2004)
Hegemonic and counter-hegemonic politics are inherent in most human groupings, particularly where such politics are geared toward the appropriation of space. Against this backdrop, the paper attempts to explain how an elite and counter-elite dichotomy in a social formation arose in the struggle for power. Contentious micro-politics in Lagos, the capital city in colonial Nigeria, with the attendant pull and push of elite bargaining for power and prominence, is examined, particularly as the dual claims to consent and dissent were reflected in the nationalist newspapers of the era.